A high spatial resolution suitability layers to support feasible power plant site selection in China - Jianxiang Shen; Rui Wang; Shihui Zhang; Jiachen Wang; Can Wang; Wenjia Cai (Scientific Data)
Abstract China is undergoing significant energy system transitions to meet carbon neutrality targets, which requires the rapid deployment of new power plants, driven by the need for large-scale renewable energy expansion and increasing electricity demand. Moreover, the policy context emphasizes the critical need for effective local land planning and integrated ecological conservation. However, current capacity expansion planning models primarily focus on provincial or regional scales and overlook key location- and technology-specific factors for feasible power plant site selection. To effectively address these challenges, we use a transparent and comprehensive assessment framework that supports high-resolution spatial analysis of power generation technologies in mainland China, named Geospatial Raster Input Data for Capacity Expansion Regional Feasibility in China (GRIDCERF-China). It provides suitability layers for 7 technologies in GeoTIFF format that can be easily integrated with various modeling tools. GRIDCERF-China fills a significant open-source data gap, offering valuable insights for regional feasible planning and decision-making while addressing diverse scientific objectives across future scenarios.